Seed Halopriming: An Efficient Technique to Improve Germination and Growth Characteristics of Ornamental Cabbage (Brassica oleracea L. var. acephala) Under Salt Stress - Azadeh Mousavi Bazaz; Hajar Nemati; Amir Ali Salavati Nik (Desert)
Germination is a critical stage of the growth of ornamental plants, which is susceptible to the adverse effects of salinity. Ornamental cabbage is one such important ornamental plants in green spaces, yet there is limited research on the effect of priming on its seed germination under saline conditions. This study investigated the effect of halopriming on the germination of this plant. The studied factors included four salinity levels with sodium chloride (0, 4, 8, and 12 dS/m) and four potassium nitrate priming levels (0, 50, 100, and 150 ppm), with three replications. Results indicated that the application of potassium nitrate ameliorated the negative effects of salinity on many of the studied traits. Germination percentage and rate at 4, 8, and 12 dS/m salinity levels with potassium nitrate priming at 50 and 100 ppm were significantly higher compared to the control (non-primed level), showing significant differences. The highest values for allometry coefficient and seedling tissue water content were obtained with the application of potassium nitrate at 100 ppm and 4 dS/m salinity level. Positive effects of potassium nitrate priming were also observed on root and shoot length, plant length, and root-to-shoot length ratio, mean daily germination, fresh and dry weight under most salinity levels. Based on the obtained results, the application of potassium nitrate at a concentration of 100 ppm had the greatest impact on mitigating the adverse effects of salinity stress on germination and seedling growth of ornamental cabbage.